Thermo-sensitive polymer, pole piece and preparation method and application of thermo-sensitive polymer and pole piece

By using temperature-sensitive polymers in polymer solid-state batteries, the plasticizer is used to break away from the main chain under high temperature triggering, the problem of thick electrode sheets being prone to cracking during baking is solved, and the effect of high ionic conductivity and cracking is achieved, which improves the energy density and manufacturing efficiency of the battery.

CN119842031APending Publication Date: 2025-04-18CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410853833.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-27
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The medium-thick electrode sheets of polymer solid-state batteries are prone to cracking during baking, resulting in limited increase in battery energy density.

Method used

The temperature-sensitive polymer is used. During the process of drying the electrode sheet, under high temperature triggering, the plasticizer group breaks away from the main chain to form a free small molecule plasticizer, optimizes the drying process, improves the ionic conductivity and inhibits the electrode sheet cracking.

Benefits of technology

It effectively improves the ionic conductivity of the electrode sheet, suppresses the tendency of the electrode sheet to crack, is especially suitable for thick electrodes, optimizes the battery manufacturing process, and reduces manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842031A_ABST
    Figure CN119842031A_ABST
Patent Text Reader

Abstract

The invention discloses a thermo-sensitive polymer, a pole piece and a preparation method and application of the thermo-sensitive polymer, the thermo-sensitive polymer comprises at least one of a compound as shown in a formula I and a compound as shown in a formula II: # imgabs0 #, and M1 and M2 are polymer soft segments respectively; r1 and R2 are respectively compound segments connected with temperature-sensitive chemical bonds; a1 and A2 are respectively temperature-sensitive chemical bonds; z1 and Z2 are each a plasticizer group; the ranges of m1 and m2 are respectively 2000 to 20000; and the ranges of n1 and n2 are respectively 200 to 5000. According to the thermo-sensitive polymer, the plasticizer is grafted to the main chain of the polymer, and after the pole piece is dried, the plasticizer group agent of the side chain of the thermo-sensitive polymer is separated from the main chain under the high-temperature triggering action to form a free micromolecular plasticizer, so that the pole piece drying process is optimized, the high ionic conductivity of the pole piece is ensured, and the service life of the pole piece is prolonged. And meanwhile, the cracking tendency of the pole piece is also inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of polymer solid-state batteries, and specifically relates to a temperature-sensitive polymer, an electrode, and a preparation method and application thereof. Background Art

[0002] With the development of electric vehicle technology and the increasing demand for battery life, the improvement of battery energy density has become an urgent issue. The most direct way to increase battery energy density is to increase the load of the pole piece. Polymer batteries have the advantages of being non-flammable, easy to process, and having a wide range of raw materials. They are the first type of commercialized batteries in the field of solid-state batteries. Unlike liquid electrolytes, solid electrolytes do not have wettability. During the preparation of electrodes, they need to be mixed with active materials, conductive agents, and binders to form a slurry. In order to ensure that the electrode has a high ionic conductivity, more electrolytes are usually added, which will result in poor dispersion of the slurry and a high solvent content. As the pole piece load increases, the thickness of the electrode increases, the absolute content of the solvent per unit increases, and the volatilization amount per unit time increases. Therefore, a large number of small solvent molecules further reduce the adhesion of the polymer, which causes the thick electrode sheet coating to crack easily during baking.

[0003] In order to solve the problem of thick electrodes being prone to cracking, on the one hand, from the perspective of the baking process, the idea of ​​in-situ polymerization of the electrolyte to form a solid electrolyte can be adopted to achieve zero solvent volatilization, thereby avoiding the problem of cracking of the electrode due to solvent volatilization. However, the problems brought about by this method are: the processability of the electrode is reduced, the internal polymerization degree and polymerization uniformity are difficult to ensure, and the electrode is porous and has solvent residues. On the other hand, from the perspective of the electrode structure, a porous and ordered electrolyte structure can be used as a skeleton, and active particles are filled into it to prepare a thick electrode. Although this method can increase the load while ensuring the morphology, there are problems such as uneven dispersion of active particles, large impedance of the active particle-porous skeleton interface, difficult skeleton molding process, and poor structural stability. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the purpose of the present application is to propose a thermosensitive polymer, an electrode, and a preparation method and application thereof. The thermosensitive polymer of the present application grafts a plasticizer onto the polymer main chain. After the electrode is dried, under the action of high temperature triggering, the plasticizer group of the side chain of the thermosensitive polymer is separated from the main chain to form a free small molecule plasticizer, thereby optimizing the electrode drying process, ensuring the high ionic conductivity of the electrode, and suppressing the cracking tendency of the electrode, which is particularly suitable for thick electrodes.

[0005] In one aspect of the present application, the present application proposes a thermosensitive polymer. According to an embodiment of the present application, the thermosensitive polymer includes at least one of a compound as shown in Formula I and a compound as shown in Formula II:

[0006]

[0007] Among them, M 1 and M 2 Each independently is a polymer soft segment;

[0008] R 1 and R 2 Each is independently a compound segment connected to a temperature-sensitive chemical bond;

[0009] A 1 and A 2 Each is independently a temperature-sensitive chemical bond;

[0010] Z 1 and Z 2 each independently a plasticizer group;

[0011] m 1 and m 2 The range of each independently is 2000 to 20000;

[0012] n 1 and n 2 The range of each is independently 200 to 5000.

[0013] According to the thermosensitive polymer of the embodiment of the present application, the thermosensitive polymer is a block copolymer, including a soft segment and a hard segment, and the plasticizer group is used as a side chain, and is bonded to the main chain through a thermosensitive chemical bond. During the mixing and baking process of the pole piece, the structure of the thermosensitive polymer can remain stable; under the high temperature triggering effect, the plasticizer group of the side chain of the thermosensitive polymer is separated from the main chain to form a free small molecule plasticizer, thereby effectively improving the ionic conductivity of the pole piece. Therefore, when the thermosensitive polymer of the present application is used for the pole piece, firstly, the use of the thermosensitive polymer of the present application enables the pole piece to withstand a higher baking temperature, optimizes the manufacturing process of the pole piece, shortens the manufacturing time and reduces the manufacturing cost. Secondly, during the baking process of the pole piece, the plasticizer group exists in the form of a side chain of the thermosensitive polymer, and there is no problem of floating of small plasticizer molecules, which makes the pole piece dispersed evenly. Most importantly, there are no free plasticizer small molecules in the mixing and baking process of the electrode to reduce the viscosity between the polymer and the active particles and between the polymer and the current collector, which greatly suppresses the cracking tendency of the electrode while ensuring high ionic conductivity, especially the cracking phenomenon of thick electrodes.

[0014] In addition, the temperature-sensitive polymer according to the above embodiment of the present application may also have the following additional technical features:

[0015] In some embodiments of the present application, the polymer soft segment includes at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, polyacrylonitrile, polypropylene carbonate, polyethylene oxide and ethylene oxide-propylene oxide copolymer.

[0016] In some embodiments of the present application, the temperature-sensitive chemical bond includes at least one of a hydrogen bond, an azo bond, and a disulfide bond.

[0017] In some embodiments of the present application, the compound segment connecting the temperature-sensitive chemical bonds includes at least one of azo compounds, disulfide compounds, urea, thiourea, 1,3-propanedioic acid, pyridine, piperidine, tetrahydropyrrole and tetrahydropyrrole derivatives.

[0018] In some embodiments of the present application, the plasticizer group includes at least one of linear ether organic matter, cyclic ether organic matter and benzene ring organic matter.

[0019] In some embodiments of the present application, the linear ether organic compound includes at least one of the compounds shown in Formula III:

[0020]

[0021] Wherein, a is equal to 0 or 1; b is equal to 0 or 1; y ranges from 1 to 25 and is an integer.

[0022] In some embodiments of the present application, the cyclic ether organic compound includes at least one of the compounds shown in Formula IV:

[0023]

[0024] Among them, R 3 =(CH 2 ) 3 X, X is F, Cl or OH, n 3 The range is 5 to 80 and is an integer.

[0025] In some embodiments of the present application, the benzene ring organic compound includes at least one of the compounds shown in Formula V:

[0026]

[0027] Among them, R 4 H or SH; R 5 OH, NH or O-(CH 2 ) X -R 6 ; R 6is CN or an ether polymer; x ranges from 0 to 10 and is an integer.

[0028] In some embodiments of the present application, at least one of the following compounds is included:

[0029]

[0030]

[0031] In the second aspect of the present application, the present application proposes a pole piece. According to an embodiment of the present application, the pole piece includes a current collector; an active material layer, the active material layer is arranged on at least one side of the current collector, and the active material layer includes an active substance, a conductive agent, a plasticizer and a residual polymer formed by the disconnection of the temperature-sensitive chemical bonds of the thermosensitive polymer described in the above embodiment, and an electrolyte salt. Therefore, firstly, the thermosensitive polymer contained in the pole piece of the present application will not decompose at a higher baking temperature, so that the pole piece can withstand a higher baking temperature, thereby optimizing the manufacturing process of the pole piece, shortening the manufacturing time and reducing the manufacturing cost. Conventional plasticizers are easy to decompose at higher baking temperatures, so existing pole pieces cannot use higher baking temperatures. Secondly, during the baking process of the pole piece, the plasticizer group exists in the form of a side chain of the thermosensitive polymer, and there is no problem of floating of small plasticizer molecules, which makes the pole piece dispersed evenly. Most importantly, there are no free plasticizer small molecules in the mixing and baking process of the electrode to reduce the viscosity between the polymer and the active particles and between the polymer and the current collector, which greatly suppresses the cracking tendency of the electrode while ensuring high ionic conductivity, and is particularly suitable for thick electrodes.

[0032] In addition, the pole piece according to the above embodiment of the present application may also have the following additional technical features:

[0033] In some embodiments of the present application, the electrode sheet is a positive electrode sheet, and the positive electrode sheet includes a positive electrode collector; a positive electrode active layer, and the positive electrode active layer is arranged on at least one side of the positive electrode collector, and the positive electrode active layer includes a positive electrode active material, a positive electrode conductive agent, the temperature-sensitive polymer and an electrolyte salt.

[0034] In some embodiments of the present application, the mass ratio of the positive electrode active material, the conductive agent, the temperature-sensitive polymer and the electrolyte salt is (50-90): (1-10): (10-25): (0-10).

[0035] In some embodiments of the present application, the single-sided loading of the positive electrode active layer is 20 mg / cm 2 ~50mg / cm 2; and / or, the single-sided thickness of the positive electrode active layer is 130 μm to 300 μm; and / or, the compaction density of the positive electrode active layer is 2.2 g / cm 3 ~2.6g / cm 3 .

[0036] In the third aspect of the present application, the present application proposes a method for preparing the pole piece of the above embodiment. According to the embodiment of the present application, the above method includes:

[0037] The active material, the conductive agent, the temperature-sensitive polymer described in the above embodiment, the electrolyte salt and the solvent are mixed to form a slurry;

[0038] The slurry is coated on at least one side of a current collector, the solvent is removed, and the electrode is heated at a high temperature to obtain a pole piece.

[0039] According to the method for preparing the pole piece of the embodiment of the present application, the thermosensitive polymer will not decompose during the drying process of the pole piece, so that the pole piece can withstand higher baking temperatures. At the same time, during the baking process of the pole piece, the plasticizer group exists in the form of a side chain of the thermosensitive polymer, and there is no problem of floating of the plasticizer small molecules, which makes the pole piece dispersed evenly. Most importantly, the absence of free plasticizer small molecules in the mixing and baking process of the pole piece reduces the viscosity between the polymer and the active particles and the viscosity between the polymer and the current collector, which greatly suppresses the cracking tendency of the pole piece while ensuring high ionic conductivity, and is particularly suitable for thick electrodes.

[0040] In addition, the method according to the above embodiment of the present application may also have the following additional technical features:

[0041] In some embodiments of the present application, the removing of the solvent comprises: vacuum drying at 40°C to 60°C for 1 hour to 3 hours; vacuum drying at 80°C to 120°C for 4 hours to 12 hours.

[0042] In some embodiments of the present application, the temperature of the high temperature heating is 180° C. to 240° C., and the time of the high temperature heating is 10 min to 20 min.

[0043] In the fourth aspect of the present application, the present application proposes a polymer solid-state battery. According to an embodiment of the present application, the polymer solid-state battery includes the pole piece described in the above embodiment or includes the pole piece made by the method described in the above embodiment. As a result, the energy density of the polymer solid-state battery is effectively improved, while also avoiding the problem of easy cracking of the thick pole piece coating during baking.

[0044] In the fifth aspect of the present application, the present application proposes an electric device. According to an embodiment of the present application, the electric device has the above-mentioned polymer solid-state battery. Therefore, the electric device has all the advantages of the polymer solid-state battery, which will not be repeated here.

[0045] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0047] Figure 1 This is a morphology image of the positive electrode sheet prepared in Example 1;

[0048] Figure 2 This is a morphology picture of the positive electrode sheet prepared in Comparative Example 1. DETAILED DESCRIPTION

[0049] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.

[0050] For polymer solid-state batteries, in the absence of additional binder addition, there are two main reasons for the cracking of thick electrodes. One is that the amount of solvent volatilization during baking is too large, and the other is that the polymer itself has insufficient adhesion. Adding plasticizers can reduce the viscosity of the slurry and thus reduce the solvent content. However, when the content of solid polymer electrolyte (SPE) in the pole piece is low (accounting for less than 13%), the plasticizer has little effect on the viscosity of the slurry, but it will greatly reduce the crystallinity of the solid polymer electrolyte and its adhesion to the active particles. After research, the inventors found that plasticizers are one of the main causes of thick electrode cracking. When the content of other formulas remains unchanged, the higher the plasticizer content, the greater the degree of cracking of the pole piece. At present, no one has solved the problem of thick electrode cracking from the perspective of plasticizers.

[0051] In view of this, in one aspect of the present application, the present application proposes a thermosensitive polymer. According to an embodiment of the present application, the thermosensitive polymer includes at least one of a compound as shown in Formula I and a compound as shown in Formula II:

[0052]

[0053] Among them, M 1 and M 2 Each independently is a polymer soft segment; As the polymer hard segment, R 1 and R 2 Each independently is a compound segment connected to a temperature-sensitive chemical bond; A 1 and A2 Each is independently a temperature-sensitive chemical bond; Z 1 and Z 2 Each is independently a plasticizer group; m 1 and m 2 The range of each is independently 2000 to 20000; n 1 and n 2 The range of each is independently 200 to 5000. The temperature-sensitive polymer proposed in this application is described in detail below:

[0054] The thermosensitive polymer provided in the present application is a block copolymer, including a soft segment and a hard segment, wherein the soft segment is a conventional solid-state battery polymer, and the hard segment is a polypropylene-based polymer grafted with a plasticizer. The plasticizer group is a branched chain and is bonded to the main chain through a thermosensitive chemical bond. During the mixing and baking process of the pole piece, the structure of the thermosensitive polymer can remain stable; under the high temperature triggering effect, the plasticizer group of the side chain of the thermosensitive polymer is separated from the main chain to form a free small molecule plasticizer, thereby effectively reducing the crystallinity of the polymer, improving its own flow, and then improving the migration rate of lithium ions dissolved in the polymer, and improving the ionic conductivity of the pole piece. Therefore, when the thermosensitive polymer of the present application is used for the pole piece, first, the thermosensitive polymer of the present application will not decompose at a higher baking temperature, so that the pole piece can withstand a higher baking temperature. Conventional plasticizers are easy to decompose at higher baking temperatures, so the existing pole piece cannot use a higher baking temperature. Therefore, the use of thermosensitive polymers allows the pole piece to withstand higher baking temperatures, optimizes the manufacturing process of the pole piece, shortens the manufacturing time and reduces the manufacturing cost. Secondly, during the baking process of the electrode, the plasticizer group exists in the form of a side chain of the thermosensitive polymer, and there is no problem of small plasticizer molecules floating up, which makes the electrode dispersion uniform. Most importantly, during the mixing and baking process of the electrode, there are no free small plasticizer molecules, which reduces the viscosity between the polymer and the active particles and between the polymer and the current collector, greatly suppressing the cracking tendency of the electrode while ensuring high ionic conductivity, which is particularly suitable for thick electrodes.

[0055] In the embodiments of the present application, the above M 1 and M 2Each of them is independently a polymer soft segment. The specific type of the above polymer soft segment is not particularly limited. As some preferred schemes, the above polymer soft segment includes at least one of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), polypropylene carbonate (PPC), polyethylene oxide (PEO) and ethylene oxide-propylene oxide copolymer (PEO-PO). When the above polymer soft segment is an ether polymer such as polyethylene oxide (PEO) or ethylene oxide-propylene oxide copolymer (PEO-PO), the general formula of the formed thermosensitive polymer is Formula II, otherwise the general formula of the formed thermosensitive polymer is Formula I.

[0056] In the embodiments of the present application, the temperature-sensitive chemical bond refers to a bond that is easily broken under high temperature triggering.

[0057] In the embodiments of the present application, the plasticizer is grafted onto the main chain through a thermosensitive chemical bond. As some preferred schemes, the thermosensitive chemical bond includes at least one of a hydrogen bond, an azo bond and a disulfide bond. Thus, the thermosensitive chemical bonds of the above types are easily broken under the action of high temperature triggering, so that the plasticizer group having the thermosensitive polymer side chain of the thermosensitive chemical bond can be easily separated from the main chain due to the breaking of the thermosensitive chemical bond to form a free small molecule plasticizer. Among them, azo bonds and disulfide bonds are both covalent bonds, and hydrogen bonds (also called van der Waals forces) are non-covalent bonds, and molecules are connected by mutual attraction. In addition, the hydrogen bond can be represented by a dotted line. Indicates, for example The dashed lines represent hydrogen bonds.

[0058] In the embodiment of the present application, the compound segment R connected with the temperature-sensitive chemical bond 1 and R 2 Condensed in The side chains of the thermosensitive polymer form a hard segment. As some preferred schemes, the compound segments connected with the thermosensitive chemical bonds include at least one of azo compounds, disulfide compounds, urea, thiourea, 1,3-propanedioic acid, pyridine, piperidine, tetrahydropyrrole and tetrahydropyrrole derivatives. Therefore, the compound segments of the above types can form thermosensitive chemical bonds with the plasticizer groups that are easily broken under high temperature triggering, so that the plasticizer groups of the thermosensitive polymer side chains can be easily separated from the main chain due to the breaking of the thermosensitive chemical bonds to form free small molecule plasticizers.

[0059] In an embodiment of the present application, the above-mentioned plasticizer group includes at least one of a linear ether organic compound, a cyclic ether organic compound and a benzene ring organic compound. According to some specific embodiments of the present application, the linear ether organic compound includes at least one of the compounds shown in Formula III:

[0060]

[0061] Wherein, a is equal to 0 or 1, indicating the number of methyl groups here; b is equal to 0 or 1, indicating the number of methyl groups here; y ranges from 1 to 25 and is an integer. The linear ether plasticizer of the structure shown in the above formula III acts as a branch chain and is bonded to the main chain through a thermosensitive chemical bond to form a plasticizer group. During the mixing and baking process of the electrode, the structure of the thermosensitive polymer containing the above plasticizer group can remain stable; under the action of high temperature triggering, the plasticizer group of the side chain of the thermosensitive polymer can be separated from the main chain to form a free small molecule plasticizer.

[0062] According to some further specific embodiments of the present application, the above-mentioned cyclic ether organic compound includes at least one of the compounds shown in Formula IV:

[0063]

[0064] Among them, R 3 =(CH 2 ) 3 X, X is F, Cl or OH, n 3 The range is 5 to 80 and is an integer. The cyclic ether plasticizer of the structure shown in the above formula IV is used as a side chain and is combined with the main chain through a thermosensitive chemical bond to form a plasticizer group. During the mixing and baking process of the electrode, the structure of the thermosensitive polymer containing the above plasticizer group can remain stable; under the high temperature triggering effect, the plasticizer group of the side chain of the thermosensitive polymer can be separated from the main chain to form a free small molecule plasticizer.

[0065] According to some further specific embodiments of the present application, the above-mentioned benzene ring organic compound includes at least one of the compounds shown in Formula V:

[0066]

[0067] Among them, R 4 H or SH; R 5 OH, NH or O-(CH 2 ) X -R 6 ; R 6 is CN or an ether polymer; x ranges from 0 to 10 and is an integer. The cyclic ether plasticizer of the structure shown in the above formula V is used as a side chain and is combined with the main chain through a thermosensitive chemical bond to form a plasticizer group. During the mixing and baking process of the electrode, the structure of the thermosensitive polymer containing the above plasticizer group can remain stable; under the action of high temperature triggering, the plasticizer group of the side chain of the thermosensitive polymer can be separated from the main chain to form a free small molecule plasticizer.

[0068] In the embodiments of the present application, the specific type of the thermosensitive polymer is not particularly limited. As some preferred schemes, the thermosensitive polymer includes at least one of the following compounds:

[0069]

[0070] The above-mentioned thermosensitive polymers are all block copolymers, including soft segments and hard segments. During the mixing and baking process of the electrode, the structures of the above-mentioned thermosensitive polymers have good stability; under the high temperature triggering effect, the plasticizer groups of the side chains of the above-mentioned thermosensitive polymers can be separated from the main chain to form free small molecule plasticizers, thereby effectively improving the ionic conductivity of the electrode.

[0071] In the embodiments of the present application, the preparation method of the thermosensitive polymer is not particularly limited. As a specific example, the preparation method of the thermosensitive polymer is as follows:

[0072] Using ATRP as an initiator, the main chain of the thermosensitive polymer is prepared by free radical polymerization of the polymer soft segment and the polymer hard segment.

[0073] The thermosensitive polymer is obtained by condensing the active functional groups such as carboxyl, amino, hydroxyl, etc. on the plasticizer of the thermosensitive chemical bond chain with the carboxylic acid on the hard segment under the catalysis of metals such as antimony.

[0074] In the second aspect of the present application, the present application proposes a pole piece. According to an embodiment of the present application, the pole piece includes a current collector; an active material layer, the active material layer is arranged on at least one side of the current collector, and the active material layer includes an active substance, a conductive agent, a plasticizer and a residual polymer formed by the breaking of the temperature-sensitive chemical bonds of the thermosensitive polymer described in the above embodiments, and an electrolyte salt. Therefore, firstly, the thermosensitive polymer contained in the pole piece of the present application will not decompose at a higher baking temperature, so that the pole piece can withstand a higher baking temperature, thereby optimizing the manufacturing process of the pole piece, shortening the manufacturing time and reducing the manufacturing cost. Conventional plasticizers are easy to decompose at higher baking temperatures, so existing pole pieces cannot use higher baking temperatures. Secondly, during the baking process of the pole piece, the plasticizer group exists in the form of a side chain of the thermosensitive polymer, and there is no problem of floating of small plasticizer molecules, which makes the pole piece dispersed evenly. Most importantly, there are no free plasticizer small molecules in the mixing and baking process of the electrode to reduce the viscosity between the polymer and the active particles and between the polymer and the current collector, which greatly suppresses the cracking tendency of the electrode while ensuring high ionic conductivity, and is particularly suitable for thick electrodes.

[0075] In the embodiments of the present application, the above-mentioned thermosensitive polymer can be applied to both the positive electrode sheet and the negative electrode sheet. Whether the above-mentioned thermosensitive polymer is applied to the positive electrode sheet or the negative electrode sheet, the above-mentioned technical effects can be achieved. According to some specific embodiments of the present application, if the above-mentioned electrode sheet is a positive electrode sheet, the positive electrode sheet includes a positive electrode current collector; a positive electrode active layer, and the positive electrode active layer is disposed on at least one side of the positive electrode current collector. The positive electrode active layer includes a positive electrode active material, a positive electrode conductive agent, a thermosensitive polymer, and an electrolyte salt.

[0076] In the embodiments of the present application, the material of the above-mentioned positive electrode current collector is not particularly limited. As some preferred solutions, the above-mentioned positive electrode current collector includes at least one of aluminum foil, aluminum foam, carbon-coated aluminum foil, carbon mesh, and carbon cloth.

[0077] According to some specific embodiments of the present application, the thickness of the above-mentioned positive electrode current collector can be 8 μm to 25 μm.

[0078] According to still some specific embodiments of the present application, the mass ratio of the positive electrode active material, the positive electrode conductive agent, the thermosensitive polymer, and the electrolyte salt is (50-90):(1-10):(10-25):(0-10), and the content of the electrolyte salt is greater than 0. By limiting the mass ratio of each component within the above range, it can be further ensured that the electrode sheet can withstand a higher baking temperature, thereby optimizing the manufacturing process of the electrode sheet, shortening the manufacturing time and reducing the manufacturing cost; at the same time, further avoiding the problem of small plasticizer molecules floating up; further ensuring that there are no small molecules in the entire manufacturing process of the electrode sheet to reduce the viscosity between the polymer and the active particles and the viscosity between the polymer and the current collector, greatly suppressing the cracking tendency of the electrode sheet while ensuring high ionic conductivity, and is particularly suitable for thick electrodes.

[0079] In the embodiments of the present application, the specific type of the above-mentioned positive electrode active material is not particularly limited, and those skilled in the art can select according to actual needs. As some preferred solutions, the above-mentioned positive electrode active material includes lithium cobaltate (LiCoO 2 ), lithium nickelate (LiNiO 2 ), lithium iron phosphate (LiFePO 4 ), lithium cobalt phosphate (LiCoPO 4 ), lithium manganese phosphate (LiMnPO 4 ), lithium nickel phosphate (LiNiPO 4 ), lithium manganate (LiMnO 2 ), binary material LiNi x A (1-x) O 2 (where A is selected from one of Co and Mn, 0 < x < 1), ternary material LiNi m B n C (1-m-n) O2 (Wherein, B and C are independently selected from at least one of Co, Al, and Mn, and B and C are different, 0 <m<1,0<n<1)。

[0080] In the embodiments of the present application, the specific type of the above-mentioned positive electrode conductive agent is not particularly limited, and those skilled in the art can select it according to actual needs. As some preferred schemes, the positive electrode conductive agent includes at least one of acetylene black, Super P, Super S, graphene, carbon fiber, carbon nanotubes, and Ketjen black.

[0081] In the embodiments of the present application, the specific type of the electrolyte salt is not particularly limited, and those skilled in the art can select it according to actual needs. For example, when the electrode is applied to a lithium-ion battery, the electrolyte salt is a lithium salt. Correspondingly, when the electrode is applied to a sodium-ion battery, the electrolyte salt is a sodium salt. As some specific examples, when the electrolyte salt is a lithium salt, the lithium salt can be at least one of an organic lithium salt and an inorganic lithium salt, such as LiPF 6 , LiBF 4 、LiClO 4 、LiAsF 6 , LiTFSI, LiFSI, LiBOB, LiDFOB, LiTFOP.

[0082] According to some specific embodiments of the present application, the single-sided loading of the positive electrode active layer is 20 mg / cm 2 ~50mg / cm 2 , thereby ensuring that the positive electrode active layer has high ionic conductivity and high loading capacity, while also greatly suppressing the cracking tendency of the electrode piece.

[0083] According to some specific embodiments of the present application, the single-sided thickness of the positive electrode active layer is 130 μm to 300 μm, thereby ensuring that the positive electrode active layer has high ionic conductivity and high loading capacity while greatly suppressing the cracking tendency of the electrode sheet.

[0084] According to some specific embodiments of the present application, the compaction density of the positive electrode active layer is 2.2 g / cm 3 ~2.6g / cm 3 , thereby ensuring that the positive electrode active layer has high ionic conductivity and high loading capacity, while also greatly suppressing the cracking tendency of the electrode piece.

[0085] In the third aspect of the present application, the present application proposes a method for preparing the pole piece of the above embodiment. According to the embodiment of the present application, the above method includes:

[0086] S100: Slurry formation

[0087] In this step, the active material, the conductive agent, the above-mentioned temperature-sensitive polymer, the electrolyte salt and the organic solvent are mixed to form a slurry.

[0088] According to some specific embodiments of the present application, the solid content of the slurry may be 30 wt% to 55 wt%, preferably 40 wt% to 45 wt%.

[0089] S200: Apply the slurry to at least one side of the current collector, remove the solvent, and heat at high temperature

[0090] In this step, the slurry is applied to at least one side of the current collector, the solvent is removed, and the electrode is heated at a high temperature to obtain a pole piece. As a specific example, the slurry can be evenly applied to the current collector by scraping.

[0091] According to some specific embodiments of the present application, the above-mentioned removal of solvent includes: vacuum drying at 40°C to 60°C for 1h to 3h to remove a large amount of solvent; vacuum drying at 80°C to 120°C for 4h to 12h to remove residual solvent. By adopting a gradient drying method, the solvent in the slurry coated on the current collector can be effectively removed, and the thermosensitive polymer of the present application will not decompose at the above-mentioned drying temperature, so that the pole piece can withstand a higher baking temperature. At the same time, during the above-mentioned drying process of the pole piece, the plasticizer group exists in the form of a side chain of the thermosensitive polymer, and there is no problem of floating of small plasticizer molecules, which makes the pole piece dispersed evenly.

[0092] According to some further specific embodiments of the present application, the temperature of high-temperature heating is 180°C to 240°C, and the time of high-temperature heating is 10min to 20min, thereby ensuring that under the above-mentioned high-temperature triggering action, the plasticizer group of the thermosensitive polymer side chain in the electrode is separated from the main chain to form a free small molecule plasticizer, which can effectively reduce the crystallinity of the polymer, enhance its own flow, and then enhance the migration rate of lithium ions dissolved in the polymer, thereby enhancing the ionic conductivity of the electrode.

[0093] Furthermore, the above method also includes:

[0094] By rolling the above-mentioned electrode sheet at 30°C to 60°C, a positive electrode sheet with high ion conductivity, high load and no cracking can be obtained.

[0095] According to the method for preparing the pole piece of the embodiment of the present application, the thermosensitive polymer will not decompose during the drying process of the pole piece, so that the pole piece can withstand higher baking temperatures. At the same time, during the baking process of the pole piece, the plasticizer group exists in the form of a side chain of the thermosensitive polymer, and there is no problem of floating of the plasticizer small molecules, which makes the pole piece dispersed evenly. Most importantly, the absence of free plasticizer small molecules in the mixing and baking process of the pole piece reduces the viscosity between the polymer and the active particles and the viscosity between the polymer and the current collector, which greatly suppresses the cracking tendency of the pole piece while ensuring high ionic conductivity, and is particularly suitable for thick electrodes.

[0096] In the fourth aspect of the present application, the present application proposes a polymer solid-state battery. According to an embodiment of the present application, the polymer solid-state battery includes the pole piece described in the above embodiment or includes the pole piece made by the method described in the above embodiment. As a result, the energy density of the polymer solid-state battery is effectively improved, while also avoiding the problem of easy cracking of the thick pole piece coating during baking.

[0097] In the fifth aspect of the present application, the present application proposes an electric device. According to an embodiment of the present application, the electric device has the above-mentioned polymer solid-state battery. Therefore, the electric device has all the advantages of the polymer solid-state battery, which will not be repeated here.

[0098] Specifically, electrical equipment may include lighting elements, display elements, mobile devices, etc., and may specifically include street lights, signal indicators, insect killer lamps, electric fans, electric toys, electric tools, battery vehicles, electric vehicles, ships, spacecraft, etc., among which electric toys may include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys and electric airplane toys, etc., and spacecraft may include airplanes, rockets, space shuttles and spacecraft, etc.; photovoltaic power generation systems may include large-scale ground photovoltaic power generation systems, distributed photovoltaic power generation and building integrated photovoltaic power generation systems, etc.

[0099] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.

[0100] Example 1

[0101] (1) Lithium iron phosphate is selected as the positive electrode active material, Super P is used as the conductive agent, and lithium bis(trifluoromethanesulfonyl)imide is used as the lithium salt, and the mixture is dissolved in N,N-dimethylformamide together with the temperature-sensitive polymer to prepare a positive electrode slurry, wherein the solid content of the positive electrode slurry is 42 wt %. The mass ratio of the positive electrode active material, the conductive agent, the temperature-sensitive polymer, and the lithium salt is 80:2:13.5:4.5.

[0102] Among them, the structure of the thermosensitive polymer is as follows:

[0103]

[0104] Among them, polyethylene oxide is the soft segment, the polyacrylate of 1,3-propanedioic acid condensed in the side chain is the hard segment, and ethylene glycol-1-methyl ether is the plasticizer, and the plasticizer is grafted to the main chain through hydrogen bonds.

[0105] (2) Use a scraper coating method to evenly apply the positive electrode slurry on the current collector.

[0106] (3) A gradient baking method is used, first vacuum drying at 50°C for 2 h, then vacuum drying at 100°C for 10 h, and finally heating at 180°C for 20 min, so that the plasticizer on the polymer side chain is separated from the main chain under the action of heat to form free small molecules.

[0107] (4) The above-mentioned electrode sheet is rolled at 60°C to obtain a positive electrode sheet. The single-side loading of the positive electrode active layer formed on the positive electrode sheet is about 40 mg / cm 2 ; The thickness of the single-sided positive electrode material layer is 160μm.

[0108] Example 2

[0109] The preparation method of Example 2 is substantially the same as that of Example 1, except that:

[0110] The thermosensitive polymer represented by formula II-1 in Example 1 is replaced by the thermosensitive polymer represented by formula II-2:

[0111]

[0112] Polyethylene oxide is the soft segment, polyacrylate with 1,3-propanedioic acid condensed on the side chain is the hard segment, and 2-ethylchloro-dioxolane is the plasticizer, which is grafted to the main chain through hydrogen bonds.

[0113] Example 3

[0114] The preparation method of Example 3 is substantially the same as that of Example 1, except that:

[0115] The thermosensitive polymer represented by formula II-1 in Example 1 is replaced by the thermosensitive polymer represented by formula II-3:

[0116]

[0117] The polyethylene oxide is a soft segment, the polyacrylate of the side chain condensed phenyl-disulfide bond-1-phenol is a hard segment, and 1-thiol-benzene is a plasticizer, and the plasticizer is grafted to the main chain through a disulfide bond.

[0118] Example 4

[0119] The preparation method of Example 4 is substantially the same as that of Example 1, except that:

[0120] The thermosensitive polymer represented by formula II-1 in Example 1 is replaced by the thermosensitive polymer represented by formula II-4:

[0121]

[0122] Polyethylene oxide is the soft segment, polyacrylamide with azobisaminobenzene condensed on the side chain is the hard segment A, polyacrylate with 1,3-propanedioic acid condensed on the side chain is the hard segment B, 1,3-aminobenzene and 2-ethylchloro-dioxolane are plasticizers, and the plasticizers are grafted to the main chain through azo bonds and hydrogen bonds.

[0123] Example 5

[0124] The preparation method of Example 5 is substantially the same as that of Example 1, except that:

[0125] The thermosensitive polymer represented by formula II-1 in Example 1 is replaced by the thermosensitive polymer represented by formula I-1:

[0126]

[0127] Among them, polyvinylidene fluoride is the soft segment, and other structures are the same as those in Example 1.

[0128] Example 6

[0129] The preparation method of Example 6 is substantially the same as that of Example 1, except that:

[0130] The thermosensitive polymer represented by formula II-1 in Example 1 is replaced by the thermosensitive polymer represented by formula I-2:

[0131]

[0132] Among them, polytetrafluoroethylene is the soft segment, and other structures are the same as those in Example 1.

[0133] Example 7

[0134] The preparation method of Example 7 is substantially the same as that of Example 1, except that:

[0135] The thermosensitive polymer represented by formula II-1 in Example 1 is replaced by the thermosensitive polymer represented by formula I-3:

[0136]

[0137] Among them, polyacrylonitrile is the soft segment, and the other structures are the same as those in Example 1.

[0138] Example 8

[0139] The preparation method of Example 8 is substantially the same as that of Example 1, except that:

[0140] The mass ratio of the positive electrode active material, the conductive agent, the temperature-sensitive polymer and the lithium salt is 83.5:2:10:4.5.

[0141] Example 9

[0142] The preparation method of Example 9 is substantially the same as that of Example 1, except that:

[0143] The mass ratio of the positive electrode active material, the conductive agent, the temperature-sensitive polymer and the lithium salt is 78.5:2:15:4.5.

[0144] Example 10

[0145] The preparation method of Example 10 is substantially the same as that of Example 1, except that:

[0146] The mass ratio of the positive electrode active material, the conductive agent, the temperature-sensitive polymer and the lithium salt is 73.5:2:20:4.5.

[0147] Embodiment 11

[0148] The preparation method of Example 11 is substantially the same as that of Example 1, except that:

[0149] The mass ratio of the positive electrode active material, the conductive agent, the temperature-sensitive polymer and the lithium salt is 68.5:2:25:4.5.

[0150] Example 12

[0151] The preparation method of Example 12 is substantially the same as that of Example 1, except that:

[0152] The single-sided loading of the positive electrode active layer formed on the positive electrode sheet is about 20 mg / cm 2 ; The thickness of the single-sided positive electrode material layer is 80μm.

[0153] Embodiment 13

[0154] The preparation method of Example 13 is substantially the same as that of Example 1, except that:

[0155] The single-sided loading of the positive electrode active layer formed on the positive electrode sheet is about 50 mg / cm 2 ; The thickness of the single-sided positive electrode material layer is 200μm.

[0156] Embodiment 14

[0157] The preparation method of Example 14 is substantially the same as that of Example 1, except that:

[0158] (3) Finally, the mixture is heated at 210°C for 15 min to cause the plasticizer on the polymer side chain to separate from the main chain under the action of heat, forming free small molecules.

[0159] Embodiment 15

[0160] The preparation method of Example 15 is substantially the same as that of Example 1, except that:

[0161] (3) Finally, the polymer is heated at 240°C for 10 min to cause the plasticizer on the polymer side chain to separate from the main chain under the action of heat to form free small molecules.

[0162] Comparative Example 1

[0163] (1) Lithium iron phosphate is selected as the positive electrode active material, Super P is selected as the conductive agent, lithium bis(trifluoromethanesulfonyl)imide is selected as the lithium salt, 1,3-aminobenzene is selected as the plasticizer, and polyethylene oxide-polyacrylamide is selected as the polymer, and the mixture is dissolved in N,N-dimethylformamide to prepare a positive electrode slurry, wherein the solid content of the positive electrode slurry is 42wt%. The mass ratio of the positive electrode active material, the conductive agent, the polymer, the plasticizer, and the lithium salt is 80:2:9:4.5:4.5.

[0164] (2) Use a scraper coating method to evenly apply the positive electrode slurry on the current collector.

[0165] (3) Using a gradient baking method, first vacuum drying at 50°C for 2 hours, and then vacuum drying at 100°C for 10 hours to obtain an initial electrode.

[0166] (4) The initial electrode sheet is rolled at 60°C to obtain a positive electrode sheet. The single-sided loading of the positive electrode active layer formed on the positive electrode sheet is about 40 mg / cm 2 ; The thickness of the single-sided positive electrode material layer is 160μm.

[0167] The morphologies of the positive electrode sheets prepared in Examples 1 to 15 and Comparative Example 1 were photographed using a commonly used camera on the market. The results are shown in Table 1. Figure 1 This is a morphology diagram of the positive electrode sheet prepared in Example 1. Figure 2This is a morphology picture of the positive electrode sheet prepared in Comparative Example 1.

[0168] The ionic conductivity of the positive electrode sheets prepared in Examples 1 to 15 and Comparative Example 1 was tested using an electrochemical workstation. The results are shown in Table 1.

[0169] The positive electrode sheets prepared in Examples 1 to 15 and Comparative Example 1 were used to assemble soft-pack batteries. The positive electrode was the positive electrode sheet prepared in Examples 1 to 15 and Comparative Example 1, the negative electrode was lithium metal, and the electrolyte was polyethylene oxide PEO, whose relative atomic mass Mn=6*10 5 g / mol), the lithium salt is lithium bis(trifluoromethylsulfonyl)imide LiTFSI, the plasticizer is acetonitrile, and the mass ratio of PEO, lithium salt and acetonitrile is 0.5:0.25:0.25. Conventional electrochemical performance tests were performed on the soft-pack batteries of Examples 1 to 15 and Comparative Example 1, respectively. The test voltage is specified to be 2.5V to 3.8V, and the charge and discharge rate is 0.5C. The test results are shown in Table 1.

[0170] Table 1

[0171]

[0172]

[0173] It can be seen from Table 1 that the pole piece of Comparative Example 1 is severely cracked, while the pole pieces of Examples 1 to 15 of the present application are uniform and not cracked. It can be seen that Examples 1 to 15 of the present application, by introducing a thermosensitive polymer during the preparation of the pole piece, can reduce the viscosity between the polymer and the active particles and the viscosity between the polymer and the current collector without small molecules in the entire process of the pole piece, thereby greatly suppressing the cracking tendency of the pole piece while ensuring high ionic conductivity.

[0174] It can also be seen from Table 1 that, compared with Examples 1 to 3, the 60°C pole piece ionic conductivity and the corresponding number of cycles of 0.2C / 80% capacity retention rate of Example 4 are further improved, and the 0.1C polarization of Example 4 is further reduced. It can be seen that increasing the types of plasticizers in the temperature-sensitive polymer can slightly improve the rate and cycle performance of the battery, which may be due to the synergistic optimization of the pole piece microstructure by multiple types of plasticizers.

[0175] By comparing Example 1 with Examples 5 to 6, it can be seen that the soft segment structure has no significant effect on the ionic conductivity of the electrode, but will affect the adhesion inside the electrode, thereby affecting the cycle performance of the battery.

[0176] By comparing Example 1 and Examples 8 to 11, it can be seen that the higher the proportion of active material in the composite positive electrode formula, the greater the polarization, and the higher the electrolyte content, the easier it is to form a complete ion conduction path, thereby improving the ion conductivity of the electrode.

[0177] By comparing Example 1 and Examples 12 to 13, it can be seen that the higher the active material loading in the composite positive electrode formula, the greater the battery polarization, resulting in a decrease in the overall battery performance.

[0178] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0179] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A thermosensitive polymer, characterized in that Including at least one of the compound shown in formula I and the compound shown in formula II: Wherein, M1 and M2 are each independently a polymer soft segment; R1 and R2 are each independently a compound segment connecting a temperature-sensitive chemical bond; A1 and A2 are each independently a temperature-sensitive chemical bond; Z1 and Z2 are each independently a plasticizer group; The range of m1 and m2 is independently 2000 to 20000; The ranges of n1 and n2 are each independently 200 to 5000.

2. The thermosensitive polymer according to claim 1, characterized in that The polymer soft segment includes at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, polyacrylonitrile, polypropylene carbonate, polyethylene oxide and ethylene oxide-propylene oxide copolymer.

3. The thermosensitive polymer according to claim 1, characterized in that The temperature-sensitive chemical bond includes at least one of a hydrogen bond, an azo bond and a disulfide bond.

4. The thermosensitive polymer according to claim 1, characterized in that The compound segment connecting the temperature-sensitive chemical bonds includes at least one of azo compounds, disulfide compounds, urea, thiourea, 1,3-propanedioic acid, pyridine, piperidine, tetrahydropyrrole and tetrahydropyrrole derivatives.

5. The thermosensitive polymer according to any one of claims 1 to 4, characterized in that The plasticizer group includes at least one of linear ether organic matter, cyclic ether organic matter and benzene ring organic matter.

6. The thermosensitive polymer according to claim 5, characterized in that The linear ether organic compound includes at least one of the compounds shown in Formula III: Wherein, a is equal to 0 or 1; b is equal to 0 or 1; y ranges from 1 to 25 and is an integer.

7. The thermosensitive polymer according to claim 5, characterized in that The cyclic ether organic compound includes at least one of the compounds shown in Formula IV: Wherein, R3=(CH2)n3X, X is F, Cl or OH, and n3 ranges from 5 to 80 and is an integer.

8. The thermosensitive polymer according to claim 5, characterized in that The benzene ring organic compound includes at least one of the compounds shown in Formula V: Wherein, R4 is H or SH; R5 is OH, NH or O-(CH2) X -R6; R6 is CN or an ether polymer; x ranges from 0 to 10 and is an integer.

9. The thermosensitive polymer according to any one of claims 1 to 4, characterized in that Includes at least one of the following compounds:

10. A pole piece, characterized in that: include: current collector; An active material layer is disposed on at least one side of the current collector, and comprises an active substance, a conductive agent, a plasticizer and a residual polymer formed by breaking the temperature-sensitive chemical bonds of the temperature-sensitive polymer according to any one of claims 1 to 9, and an electrolyte salt.

11. The pole piece according to claim 10, characterized in that: The electrode sheet is a positive electrode sheet, and the positive electrode sheet includes a positive electrode current collector; A positive electrode active layer is disposed on at least one side of the positive electrode current collector, and the positive electrode active layer comprises a positive electrode active material, a positive electrode conductive agent, the temperature-sensitive polymer and an electrolyte salt.

12. The pole piece according to claim 11, characterized in that: The mass ratio of the positive electrode active material, the conductive agent, the temperature-sensitive polymer and the electrolyte salt is (50-90):(1-10):(10-25):(0-10).

13. The pole piece according to claim 11, characterized in that: The single-sided loading of the positive electrode active layer is 20 mg / cm 2 ~50mg / cm 2 ; And / or, the single-sided thickness of the positive electrode active layer is 130 μm to 300 μm; And / or, the compaction density of the positive electrode active layer is 2.2 g / cm 3 ~2.6g / cm 3 .

14. A method for preparing a pole piece according to any one of claims 10 to 13, comprising: Mixing an active material, a conductive agent, a temperature-sensitive polymer according to any one of claims 1 to 9, an electrolyte salt, and a solvent to form a slurry; The slurry is coated on at least one side of a current collector, the solvent is removed, and the electrode is heated at a high temperature to obtain a pole piece.

15. The method according to claim 14, characterized in that The removing of the solvent comprises: Vacuum drying at 40°C to 60°C for 1h to 3h; Vacuum dry at 80℃~120℃ for 4h~12h.

16. The method according to claim 14, characterized in that The temperature of the high temperature heating is 180° C. to 240° C., and the time of the high temperature heating is 10 min to 20 min.

17. A polymer solid-state battery, characterized in that: A pole piece comprising any one of claims 10 to 13 or a pole piece made by the method described in any one of claims 14 to 16.

18. An electrical equipment, characterized in that: A polymer solid-state battery according to claim 17.

Citation Information

Cited By

  • Temperature-sensitive polymer, electrode sheet, preparation method therefor and use thereof

    WO2026002150A1